Highly efficient magnetic targeting of mesenchymal stem cells in spinal cord injury - Vaněček V (Dove Medical Press, 2012)
Václav Vanecek,1,5 Vitalii Zablotskiim,2 Serhiy Forostyakm,1,5 Jirí Ružickam,1 Vít Herynekm,3 Michal Babic,4 Pavla Jendelová,1,5 Šárka Kubinová,1 Alexandr Dejneka,2 Eva Syková1,51Institute of Experimental Medicine AS CR, Prague, Czech Republic; 2Institute of Physics AS CR, Prague, Czech Republic; 3MR-Unit, Institute for Clinical and Experimental Medicine, Prague, Czech Republic; 4Institute of Macromolecular Chemistry AS CR, Prague, Czech Republic; 5Department of Neuroscience, 2nd Faculty of Medicine, Charles University, Prague, Czech RepublicAbstract: The transplantation of mesenchymal stem cells (MSC) is currently under study as a therapeutic approach for spinal cord injury, and the number of transplanted cells that reach the lesioned tissue is one of the critical parameters. In this study, intrathecally transplanted cells labeled with superparamagnetic iron oxide nanoparticles were guided by a magnetic field and successfully targeted near the lesion site in the rat spinal cord. Magnetic resonance imaging and histological analysis revealed significant differences in cell numbers and cell distribution near the lesion site under the magnet in comparison to control groups. The cell distribution correlated well with the calculated distribution of magnetic forces exerted on the transplanted cells in the subarachnoid space and lesion site. The kinetics of the cells’ accumulation near the lesion site is described within the framework of a mathematical model that reveals those parameters critical for cell targeting and suggests ways to enhance the efficiency of magnetic cell delivery. In particular, we show that the targeting efficiency can be increased by using magnets that produce spatially modulated stray fields. Such magnetic systems with tunable geometric parameters may provide the additional level of control needed to enhance the efficiency of stem cell delivery in spinal cord injury.Keywords: magnetism, mesenchymal stem cell, nanoparticle, spinal cord injury, modeling